Training social workers at the Master's degree level: the Italian case. - Cellini, Giovanni; Pavani, Luca (Social Work Education, 2026)
The article focuses on the complexity of social work education at Master's level in Italy. After a literature review on social work education, an exploratory research carried out between December 2021 and June 2022 is presented. The research questions are about how Italian universities provide Master's level education for social workers and the specificities of the different programmes. Admission requirements, professional profiles, disciplines and practice training are some of the issues addressed. Considering the Master's training system is characterized by an interdisciplinary approach, but provides limited focus on social work disciplines, the research study shows the need to train specialist social workers who have a strong professional identity and at the same time can take on managerial roles. These findings need to be considered in the immediate post-pandemic scenario and in the current historical stage, which is now an exceptional economic situation, that impacts on people's conditions and welfare. As the pandemic has highlighted inequalities and new needs, a structural approach is now required that goes beyond the emergency phase, also considering that new resources were put into social and health services. The conclusions highlight some future perspectives for social work education in Italy and suggest possible new research developments.